Aquaculture law and policy : towards principled access and operations - VanderZwaag, David L.; Chao, Gloria (Routledge, 2006)
The aquaculture industry is fast expanding around the globe and causing major environmental and social disruptions. The volume is about getting a 'good governance' grip on this important industry. The book highlights the numerous law and policy issues that must be addressed in the search for effective regulation of aquaculture. Those issues include among others: the equitable and fair assignment of property rights; the design of effective dispute resolution mechanisms; clarification of what maritime laws apply to aquaculture; adoption of a proper taxation system for aquaculture.
Keywords: Aquaculture -- Law and legislation.; Aquaculture -- Government policy.; LAW -- Agricultural.; Canadian aquaculture; Electronic books.